1996
DOI: 10.1111/j.1748-0361.1996.tb00768.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interactive Effects of Race and Ethnicity and Mother's Residence on the Adequacy of Prenatal Care

Abstract: Adequate prenatal care is known to reduce the risks of low birth weight and neonatal death, yet nearly one quarter of all women giving birth in the United States receive delayed, inadequate or no prenatal care. This suboptimal use of prenatal care has contributed to rates of low birth weight and neonatal mortality higher than those in most other industrialized nations. This paper examines the relationships among race/ethnicity, residence, maternal sociodemographic and medical risk characteristics, and use of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 27 publications
1
17
0
1
Order By: Relevance
“…Excessive deaths among the youngest and most vulnerable members of a society reflect inadequate resources (food, income, parental education) and infrastructure (health care facilities/practitioners, clean water, waste treatment), as well as exposure to environmental risks (toxins, infectious disease vectors, poor housing quality). Higher infant mortality rates have been found in rural than urban areas in the United States, 2–4 as well as in counties with higher levels of socioeconomic disadvantage 5 . Yet, no studies have examined whether characteristics of rurality—smaller population, geographic isolation and proximity to population concentrations—are associated with infant mortality rates when socioeconomic conditions, infrastructure, and environmental risks, often associated with mortality and rurality, are considered.…”
mentioning
confidence: 99%
“…Excessive deaths among the youngest and most vulnerable members of a society reflect inadequate resources (food, income, parental education) and infrastructure (health care facilities/practitioners, clean water, waste treatment), as well as exposure to environmental risks (toxins, infectious disease vectors, poor housing quality). Higher infant mortality rates have been found in rural than urban areas in the United States, 2–4 as well as in counties with higher levels of socioeconomic disadvantage 5 . Yet, no studies have examined whether characteristics of rurality—smaller population, geographic isolation and proximity to population concentrations—are associated with infant mortality rates when socioeconomic conditions, infrastructure, and environmental risks, often associated with mortality and rurality, are considered.…”
mentioning
confidence: 99%
“…Not only are African American women less likely to receive prenatal care compared to white women, but also they are more likely to start prenatal care in their third trimester of pregnancy (Daniels et al 2006) and have pregnancy complications (LaVeist et al 1995; Haas et al 1993). Clarke and colleagues (1995), using the same data as Miller et al (1996), found that African American women in rural areas are more likely to have late or no prenatal care compared to white and Hispanic women.…”
Section: Literature Reviewmentioning
confidence: 94%
“…Moreover, fewer Ob-Gyn doctors in rural areas translates into greater transportation (both distance and time cost) barriers and greater difficulties accessing prenatal care for rural mothers (Davis et al 2004; Braveman et al 2000). For example, Miller and colleagues (1996) found that women who live in rural areas are more likely to receive prenatal care late or not at all, regardless of their maternal risk profile.…”
Section: Literature Reviewmentioning
confidence: 99%
“…En France, la fréquence des consultations ou examens non faits pour des raisons financières a récemment augmenté, passant ainsi d'après les données d'enquêtes périnatales successives de 1,8 % en 1998 à 2,3 % en 2003 et 4,4 % en 2010 [7]. Les facteurs associés à un suivi prénatal sous-optimal identifiés sont la grande multiparité [8], l'insuffisance de revenus [9], l'appartenance à une minorité ethnique [10], le niveau socio-économique et d'éducation bas et le jeune âge maternel [11]. Dans son dernier rapport, l'Observatoire national de la pauvreté et de l'exclusion sociale (Onpes) pointait les obstacles à l'accès aux soins persistant malgré l'extension de la couverture maladie à la fin des années 1990 (couverture maladie universelle [CMU]) et observait à l'échelle nationale une hausse du renoncement aux soins pour raisons financières se concentrant sur les soins dentaires et dans une moindre mesure sur l'optique et les consultations de médecine géné-rale [12].…”
Section: Inégalités Sociales De Suivi De Grossesseunclassified